Rhetorics of Belonging : Nation, Narration, and Israel/Palestine. - Bernard, Anna. (Postcolonialism Across the Disciplines Series, 2014)
Rhetorics of Belonging describes the formation and operation of a category of Palestinian and Israeli "world literature" whose authors actively respond to the expectation that their work will "narrate" the nation, invigorating critical debates about the political and artistic value of national narration as a literary practice.